Exploring power dynamics in supply chains - Balloni, Armando (2024)
The dynamics of power and dependence in global supply chains are pivotal in shaping the operational strategies and outcomes of firms across various industries. Drawing from Resource Dependence Theory (RDT) and Institutional Theory (IT), this thesis explores the intricate interplay of strategic management practices within these frameworks, offering a new lens through which to view the impacts of power asymmetry, joint dependence, and the strategic use of global supply chains on firm behavior and performance. Resource Dependence Theory (RDT) has long emphasized the importance of power dynamics in managing dependencies to secure essential resources, which in turn shape business strategies and operational outcomes. These outcomes are influenced by factors such as Directional Dependence Asymmetry (DDA) and Joint Dependence (JD), which dictate the power imbalances and collaborative strategies within the global supply chain networks. Meanwhile, Institutional Theory (IT) adds a complementary perspective, suggesting that firms also conform to the norms and practices of their institutional environments to gain legitimacy and enhance survival prospects. This duality of influence underscores the necessity for firms to navigate not only their immediate interfirm dynamics but also broader institutional pressures. The research presented in this thesis uses detailed empirical analysis to explore how these theories manifest in real-world settings, particularly in the technology hardware and equipment industry, known for its rapid innovation and complex supply chain requirements. By integrating RDT and IT within the context of global supply chain management, we investigate how power and dependence dynamics are influenced by strategic decisions such as global sourcing and supply base diversification. This analysis is conducted through the use of comprehensive datasets derived from the Bloomberg terminal's Supply Chain Module (SPLC), focusing on publicly listed companies. This thesis uncovers how joint dependence and dependence asymmetry interact to influence strategic outcomes like inventory leanness and supplier strategies, providing insights into how firms can manage their dependencies more effectively. It also delves into how global sourcing strategies reshape power dynamics between focal firms and their suppliers, thereby influencing not only operational efficiencies but also financial performance. The findings contribute to a deeper understanding of how strategic management practices can be optimized within the rapidly evolving landscape of global supply chains. Following this introduction, the thesis is structured into several key sections, including a thorough literature review that situates the current research within the wider body of knowledge, development of theory and hypotheses, detailed description of research methodologies, presentation of data analyses and results, and a discussion section that interprets the findings within the broader context of strategic management and global supply chain dynamics. The conclusion summarizes the key contributions of the research, discusses its limitations, and suggests directions for future research. This integrated approach not only bridges the gap in literature concerning the simultaneous impact of joint dependence and directional dependence asymmetry but also offers practical guidance for managing complex supply chain networks effectively, fostering resilience, and enhancing competitive advantage in global markets.